PERSEPSI GURU TENTANG PENERAPAN MANAJEMEN SUMBER DAYA MANUSIA DENGAN EFEKTIVITAS KERJA GURU - Tiara Tiara Fur Qonita (Universitas Islam Negeri Sumatera Utara Medan, 2018)
The purpose of this research is to know the 1). Knowing the perceptions ofteachers towards the application of human resources management that are in SMK PAB 2 Helvetia Medan Labuhan Deli, 2). Find out the effectiveness of the work of the teacher in, 3). Knowing there is a signifikankah relationship between the perception of teachers about the application of human resources management with the effectiveness of the work of the teacher in. The results of this study concluded that there is a data management based on strong relationships and significant among teachers about the application of human resources management (X) and the effectiveness of the Work of teachers (Y) of 0076 with coefficient determination (r2) are obtained from the results of the calculations of0.006 which give meaning to that perception of teachers about the application of human resources management (X) gives the relationship of 0.006 x 100% = 0.6% against the effectiveness of the work of teachers (Y). The results of this study concluded that there is a data management based on strong relationships and significant among Prsepsi teachers about the application of human resources management (X) and the effectiveness of the Work of teachers (Y) of 0076 with coefficient determination (r2) are obtained from the results of the calculations of0.006 which give meaning to that perception of teachers about the application of human resources management (X) gives the relationship of 0.006 x 100% = 0.6% against the effectiveness of the work of teachers (Y). While the perception of teachers about the application of human resources management has a strong and significant relationship with the effectiveness of the work of the teacher in PAB 2 Helvetia Labuhan Deli Sub with the results of the analysis of the hypothesis it is characterized with a donation effect of 1%. While the significant value was briefly engaged both (Teacher Perceptions about the implementation of human resources management and the effectiveness of the work of the teacher) can be seen through the test of ' t